Field efficiency in diferent mechanized operations in coffee crop - Cunha, Joao Paulo Barreto; da Silva, Fabio Moreira; Dias, Rodrigo Elias Batista Almeida (Coffee Science - ISSN 1984-3909, 2016)
Coffee is a prominent culture in Brazil, so much that in recent years the coffee crop has passed major changes, such as the intensive use of mechanization that has become a viable alternative for most producers, enabling increased capacity and reduction production costs. Currently in areas totally suitable for mechanization, all operations during the crop cycle are performed mechanically by different machines and implements. This experiment was carried out in Alfenas-MG, in order to determine the work capacity and efficiency of field machines used in different mechanized operations in the coffee crop. The performance data were treated statistically by Pearson correlation (p), wich allowed to determine the influence of operating speed and average length of streets in the performance parameters. Based on the results the parameters of operating performance, effective field capacity and time required were highly correlated as the operating speed of mechanized sets. The holes preparation, raking and gathering showed the worst results of field efficiency, while other operations evaluated showed values above 70%, considered acceptable.